2012
DOI: 10.1128/cvi.00016-12
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal Immunization with a Formalin-Inactivated Human Influenza A Virus Whole-Virion Vaccine Alone and Intranasal Immunization with a Split-Virion Vaccine with Mucosal Adjuvants Show Similar Levels of Cross-Protection

Abstract: ABSTRACTThe antigenicity of seasonal human influenza virus changes continuously; thus, a cross-protective influenza vaccine design needs to be established. Intranasal immunization with an influenza split-virion (SV) vaccine and a mucosal adjuvant induces cross-protection; however, no mucosal adjuvant has been assessed clinically. Formalin-inactivated intact human and avian viruses alone (without adjuvant) induce cross-protection against the highly pathogenic H5N1 avian influenz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
29
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 34 publications
0
29
0
Order By: Relevance
“…Intranasal immunization with gammaradiation-inactivated whole-virion influenza vaccine induces influenza virus-specific cross-reactive humoral and cellular immunity (44,45). On the other hand, formalin-inactivated whole-virion influenza vaccine induces cross-reactive humoral immunity but rarely cellular immunity (24,45). Furthermore, cross-reactive neutralizing antibodies contribute to the cross-protection caused by intranasal immunization with formalin-inactivated whole-virion vaccine, and cross-reactive neutralization by intranasal immunization with a formalin-inactivated H1N1 influenza virus vaccine includes drift variants within the influenza virus subtype (24).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Intranasal immunization with gammaradiation-inactivated whole-virion influenza vaccine induces influenza virus-specific cross-reactive humoral and cellular immunity (44,45). On the other hand, formalin-inactivated whole-virion influenza vaccine induces cross-reactive humoral immunity but rarely cellular immunity (24,45). Furthermore, cross-reactive neutralizing antibodies contribute to the cross-protection caused by intranasal immunization with formalin-inactivated whole-virion vaccine, and cross-reactive neutralization by intranasal immunization with a formalin-inactivated H1N1 influenza virus vaccine includes drift variants within the influenza virus subtype (24).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, formalin-inactivated whole-virion influenza vaccine induces cross-reactive humoral immunity but rarely cellular immunity (24,45). Furthermore, cross-reactive neutralizing antibodies contribute to the cross-protection caused by intranasal immunization with formalin-inactivated whole-virion vaccine, and cross-reactive neutralization by intranasal immunization with a formalin-inactivated H1N1 influenza virus vaccine includes drift variants within the influenza virus subtype (24). However, Takada et al demonstrated that formalin-inactivated H5N1 influenza whole-virion vaccine in intranasal immunization does not induce cross-protection against different influenza virus subtypes through cross-reactive neutralizing antibodies (25).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations